CMY-13, a Novel Inducible Cephalosporinase Encoded by an Escherichia coli Plasmid - Miriagou, V. (American Society for Microbiology, 2004)
An IncN plasmid (p541) from Escherichia coli carried a Citrobacter freundii-derived sequence of 4,252 bp which included an ampC-ampR region and was bound by two directly repeated IS26 elements. ampC encoded a novel cephalosporinase (CMY-13) with activity similar to that of CMY-2. AmpR was likely functional as indicated in induction experiments.